The analysis of several types of catalysts for ozone decomposition. Issue 1 (January 2021) - Luvita, Veny; Bismo, Setijo; Sugiarto, Anto Tri
Abstract: There has been rapid technological development in the aspect of water and wastewater treatment, including the application of ozone technology, commonly known as Advanced Oxidation Processes (AOPs). This involves the use of ozone gas converted to oxygen and OH ● radicals, which possess the capacity to degrade the unwanted compounds present, although there is need for performance optimization to enhance the ease of formation and decomposition. This process is faced with serious problems that require immediate attention, particularly the presence of excess ozone, which is harmful to the health of living things, especially humans. Ozone decomposition uses an MnOx active core catalyst with a nominal loading of 0–2%. As a comparison used catalyst supports such as Zeolite Alam Lampung (ZAL), Granular Activated Carbon (GAC) and Green Sand (GS) with diameter 18–100 mesh. However, the challenge is comprehensively attenuated by using catalysts possessing the capacity to degrade the excesses, and promote procedure optimization, subsequently enhancing conversion and decomposition. Furthermore, previous studies have demonstrated the potential to elevate the production of OH radicals, and it was also established that catalysts from natural origin are less expensive, easy to operate, highly selective and difficult to damage under various conditions. The result of this study is GAC is more effective and efficient compared to others for decomposition.